Addressing the Underrepresentation of Men in Early Childhood Education: Perspectives, Barriers, and Instructional Design Solutions - Falode, Oluwole Caleb (Journal of Childhood Studies, 2026)
Addressing the underrepresentation of male early childhood educators is crucial due to their role in fostering children’s holistic development. Male educators provide unique perspectives and serve as role models in a gender-sensitive environment. This study builds on existing research through a literature review and semistructured interviews with a global sample of ECE practitioners and students. Findings reveal that social, psychological, and economic barriers contribute to the gender imbalance. Raising awareness about men’s positive impact in ECE and creating incentives for male educators are essential. Inclusive instructional designs in ECE programs can encourage gender diversity and support balanced development for young learners.